Toward improving anal health care among GBMSM in Kenya: Lessons from a patient's illness, treatment and recovery journey - Samuel Anyula Gorigo; Collins Owek; Zipporah Mwangangi; Harram Memon; Isham Umair; Pascal Macharia; John Mathenge; James Blanchard; Lyle R. McKinnon; Joshua Kimani; Stephen Moses; Parinita Bhattacharjee; et al. (Taylor & Francis Group, 2024)
We aimed to illuminate the challenges of treating anal diseases among gay, bisexual and other men who have sex with men (GBMSM) in a homophobic climate amid resource constraints. Building on a long-term Kenyan-Canadian collaboration, an anal healthcare intervention study, known as the WEMAH Project, was initiated in January 2022. The initial collaborative work strengthened existing anal health services provided at a community-based clinic serving GBMSM in Nairobi. The illness and treatment journey for one patient is highlighted. Prior to attending the community clinical programme, reluctance to disclose symptoms to other healthcare workers, misdiagnoses and incorrect treatment, absence of physical exam conducted, lack of access to effective medications, and self-treatment attempts not only led to late disease detection but also exacerbated the illness itself, culminating in advanced disease progression accompanied by severe pain and suffering. However, once connected to the community clinic with the enhanced anal healthcare programme, the disease was effectively managed by the clinical team. Although specialised clinics have been established throughout Kenya to meet the STI-related needs of GBMSM, the constellation of factors highlighted in one patient's journey, from illness to recovery, reveals important gaps in Kenya's existing sexual health programme for GBMSM.